Flavour Components and the Effects of Organic Acids Washing on the Earthy Flavour and Physical Attributes of the Black Tilapia (O. Mossambica) Fillets - Ahmad, Nurul Izzah (2000)
The selection and training of panelists for identification of earthy attributes in wild black tilapia was carried out using triangle test and Quantitative Descriptive Analysis procedures. Training was carried out in three stages. The first stage was the introduction to fish flavour characteristics while the second and third stages were the familiarization and discrimination stages, respectively. Earthy was the main characteristic for odour and flavour in freshwater fish, while shellfish, briny and sour characteristics were described for marine fish. The threshold level for geosmin was 0.lµgml-1. Earthy flavour attribute was more easily detected as compared to aroma or aftertaste attributes. The volatile flavour compounds identified in black tilapia from three different water environments (cultured pond, lake and channel) were aldehydes, ketones, alcohols, acids and esters, aromatic compounds, furans, cyclic- and hydrocarbons, Ncontaining compounds and S-containing compounds. 62 compounds were detected in cultured black tilapia, 139 in black tilapia taken from lake and 89 in black tilapia taken from channel. The major compound identified in all samples was 2,6-bis(tert-butyl)-4-methylphenol. Other abundant compounds were 1 , 1-( 6-hydroxy- 2,5-benzofurandiyl)bis-ethanone, butyl 2-methylpropyl 1 ,2-benzenedicarboxylate, hexadecanal, heptadecane and benzothiazole. The earthy flavoured compounds, geosmin and isobomeol were found in trace amount in all samples. Acetic, citric and tartaric acids washings at 0.125, 0.25, 0.5, 1 and 2% respectively, were carried out to determine their effects on the removal of the earthy odour and the physical attributes (hardness and colour) of black tilapia fillets. Washing with 0.5% citric acid resulted in fillets with acceptable hardness and colour characteristics and showed a minimum denatured muscle zone. Washing with 0.5% tartaric acid decreased (P<0.01) the hardness, while washing with 0. 5 % acetic acid increased the whiteness (P<0.05) and imparted acetic acid smell. The sensory scores showed that washing with 0.5% acetic, citric and tartaric acid respectively decreased 75, 65 and 48% of earthy odour from uncooked black tilapia fillets.